Pengembangan Bahan Ajar e-Book Berbasis Science, Environment, Technology, Society (SETS) Terintegrasi Kearifan Lokal Untuk Menunjang Kemampuan Pemecahan Masalah Peserta Didik - Nazilah, Eneng; Alamsyah, Trian Pamungkas; Suryani, Dwi Indah (PendIPA Journal of Science Education, 2025)
To improve the problem-solving skills of junior high school students, this study developed teaching materials in the form of e-Books based on the Science, Environment, Technology, and Society (SETS) approach. This approach was integrated with Banten local wisdom on the material of Elements, Compounds, and Mixtures. The development process was carried out using the ADDIE model which has five phases, namely Analyze, Design, Development, Implementation, and Evaluation. The quality of the e-Book was calculated through a validation process carried out by material experts, teaching material experts, and practitioners, while limited trials were carried out with students using a response questionnaire. The validation results proved that the e-Book had a "very valid" level of validity with a score of 90.90% in terms of content, appearance, presentation, and relevance to local wisdom. Meanwhile, student responses showed a "very positive" response with a percentage of 88.34%. This shows that the SETS-based e-Book integrated with local wisdom is worthy of being used as an alternative innovative teaching material in an effort to support students' problem-solving skills.